La théorie marxiste du salaire - Daubigney, J.; Meyer, G. (L'Actualité économique, 1980)
AbstractThis article develops and discusses the foundations of the marxist wage-theory. According to this theory, the labor force is a commodity, so it has a use value and an exchange value. Exchange value becomes a price and the wage, on a market, becomes the labor market. A detailed examination of these statements leads to several critical remarks. The main one is that the theory cannot describe and explain the contents of the value of the labor force and is unable to understand how the exchange value of labor force is changing in a price: the wage. That is a fundamental critique from the marxist epistemologic point of view, which needs a radical reconstruction of the theory.